"AMAN DI DUNIA MAYA" ANALISIS BUKU BAHASA INDONESIA KELAS TINGGI BERBASIS KELAYAKAN BUKU BSNP - Irene, Velicia Theresia; Purwati, Panca Dewi; Pasha, Lintang Revalina Islami; Habsari, Melani Dwi; Arbastra, Raditya Panji; Kusuma, Ajeng Wifa Wahyu (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to evaluate the feasibility of Chapter 8 of the Indonesian language textbook for Grade VI elementary school students entitled "Safe in Cyberspace," based on four aspects of the National Education Standards Agency (BSNP) standards: content, language, presentation, and graphics. This study uses a qualitative case study approach through documentation study techniques and content analysis. This chapter was chosen because it contains the theme of digital literacy which is important in learning Indonesian and encourages the development of students' writing and critical thinking skills. The analysis results show that Chapter 8 meets the feasibility criteria with an average score of 82%, which is classified as good. The average assessment results from the four aspects indicate that Chapter 8 is suitable for use as teaching material and can be a reference in developing adaptive and contextual textbooks. Although there are some shortcomings in the language and graphics aspects, overall this book is still suitable for use in the learning process. These findings are expected to provide input for the development of more effective textbooks that are in accordance with national education standards.